A case series shows independent vestibular labyrinthine function after major surgical trauma to the human cochlea - Stefan K. Plontke (Nature Portfolio, 2021)
Plain language summary Receptors for the hearing and balance systems are located in the inner ear. These are very delicate structures that convert sound and movement into nerve signals to control hearing and balance. Surgical damage to either system was widely believed to cause loss of function in the other. Here, we investigated the function of the balance receptors before and after severe damage to the part of the inner ear which is responsible for hearing (the cochlea) due to surgical removal of tumurs. We show that despite the close proximity of both types of receptors and the severe trauma to the cochlea, in most patients the balance system can still function normally. This observation may have important implications for how we treat patients with inner ear surgery and for the techniques we use to treat hearing and balance disorders.